EXTRAÇÃO ASSISTIDA POR ULTRASSOM APLICADA A DETERMINAÇÃO DE Cu, Fe, Mn e Zn EM CHIA (Salvia hispanica L.) POR ESPECTROMETRIA DE ABSORÇÃO ATÔMICA - Bahia, Francielly Aparecida (2019)
Recently, the consumption of chia has grown due to consumers' search for healthier foods. Chia has a diverse composition, with emphasis on the presence of proteins, which provide all the essential amino acids and this seed has no cholesterol. It is rich in vitamin B, in omega-3 and omega-6 (fatty acids), antioxidants, and has macro and microelements (Ca, Mg, P, Cu, Zn, Mn, Na and Fe). Considering the nutritional contribution resulting from the ingestion of these components to the human organism, knowledge and analysis of macro and microelements present in the chia becomes important for the consumer of this type of food. The concentration and distribution of metals in chia is still little known, but there are already studies that use ICP-MS, ICP-OES and a work that made use of Flame Atomic Absorption Spectrometry (F AAS) to detect elements in this food. However, there are still few studies reported in the literature regarding the elementary characterization of this oilseed and most studies do not present validation procedures, which give greater reliability to the developed methodologies. As a result, further research into the characterization of elemental composition of chia becomes necessary. In this sense, a simple and fast method for the determination of Cu, Fe, Mn and Zn in chia flour and seed samples using ultrasound assisted extraction and the F AAS technique was proposed. Firstly, a simplex centroid mixture design was applied to optimize the composition of the extracting solvents, indicating as optimal a mixture of 3.3 mL nitric acid and 1.7 mL of hydrogen peroxide. Other variables such as sample mass, sonication time and filtration type were optimized in univariate way. In the analysis of the sonication time it was observed that there were no significant differences on the extracted metal contents from the chia when times longer than 30 minutes were used. Thus, a time of 15 minutes of ultrasonic agitation was defined as optimal. In the analysis of the influence of the sample mass it was found that the use of 0.2 g chia results in better extraction rates for all metals. In order to evaluate the influence of the filtration type, a test was performed in which two simple filtration types were compared: filtration in plain filter paper and filtration in pleated filter paper. Among the two forms of filtration, the one with pleated paper was more efficient, because the filtration time was reduced when compared those one of the filtration on plain filter paper. Thus, the ultrasound assisted extraction method was optimized with composition of extracting solvents of 3.3 mL of nitric acid and 1.7 mL of hydrogen peroxide, sonication for 15 minutes, 0.2 g of sample and filtration in pleated paper. Subsequently, a validation study was performed in which merit figures of linearity, precision, accuracy, detection limit (LOD) and quantification limit (LOQ) were analyzed. The ultrasound assisted extraction method was simple, environmentally friendly, accurate and precise, with detection limits of 0.5 to 4 (μg g-1), good linearity with values of R2> 99% and RSD values of 4.9 to 8%, which were lower than the RSD values recommended in the literature (< 11%). To verify the accuracy of the method, the metal concentration results obtained by ultrasound assisted extraction were compared to data from dry digestion of the chia samples by applying a paired t-test at the 95% confidence level. No significant differences were observed between the compared methods for Cu, Fe and Mn analysis indicating the good accuracy of the developed extraction methodology for these metals. However, a significant difference between the compared methods was observed for Zn. This may be explained by possible losses of Zn in dry digestion due to greater manipulation of the sample by the analyst and to the use of long heating times at high temperatures. The proposed extraction procedure was then applied to 10 chia flour and seeds samples of different origins, and the average concentrations were 20 ± 1, 53 ± 3, 57 ± 3 and 57 ± 3 (μg g-1) for Cu, Fe, Mn and Zn, respectively. The determined concentrations of the metals were similar to those ones found in other studies for the same matrix. Regarding the recommended daily intake of metals through daily consumption of 25g of the chia, it presents a contribution of 505, 1320, 1412 and 1426 μg of Cu, Fe, Mn and Zn, respectively.